Ganglioside complexes containing GQ1b as targets in Miller Fisher and Guillain–Barré syndromes. Issue 10 (13th March 2008) - Kanzaki, M; Kaida, K; Ueda, M; Morita, D; Hirakawa, M; Motoyoshi, K; Kamakura, K; Kusunoki, S
Abstract : Background: Serum antibodies to GQ1b are associated with Miller Fisher syndrome (MFS) and Guillain–Barré syndrome (GBS) with ophthalmoplegia. Antibodies to ganglioside complexes (GSCs) have not yet been examined in a large population of patients with MFS or GBS. This study aimed to determine the clinical significance of antibodies to GSCs in MFS and GBS. Methods: The study investigated serum anti-GSC antibodies and the clinical features in 64 MFS patients, 53 GBS patients with ophthalmoplegia (GBS-OP(+)) and 53 GBS patients without ophthalmoplegia (GBS-OP(−)). Results: Thirty patients with MFS (47%), 25 with GBS-OP(+) (47%) and none with GBS-OP(−) had antibodies to GSCs containing GQ1b or GT1a. Patients with MFS and GBS-OP(+) were subdivided according to the antibody reactivities; patients with antibodies specific to GQ1b and/or GT1a (without anti-GSCs antibodies) were placed in Group 1, those with antibodies against GSCs with a total of two sialic acids in the terminal residues, such as GQ1b/GM1, were placed in Group 2, and those with antibodies against GSCs with a total of three sialic acids in the terminal residue, such as GQ1b/GD1a, were placed in Group 3. In MFS, sensory disturbances were infrequent in Group 2 compared with the other groups (p<0.0001). Antibodies specific to GQ1b were observed more often in MFS than in GBS-OP(+) (p = 0.0002). Conclusions: IgG antibodies to GSCs containing GQ1b or GT1a were closely associated with the development of ophthalmoplegia in GBS, as well as MFS. Both GQ1b and clustered epitopes of GSCs containing GQ1b or GT1a may be prime target antigens for MFS and GBS-OP(+).